Antara Abimelekh dan Yotam: Studi Eksegesis Hakim-Hakim 9:7-21 - Yudi Jatmiko (Sekolah Tinggi Teologi Berita Hidup, 2021)
AbstractIn the passage of Judges 9:7-21, Jotham was described as an inferior figure compared to Abimelech who was a ruler. But, here exactly lies the beauty of the narrative writing. The narrator wished to topple down and uphold the thesis that criticize Abimelech leadership, as well as approved Jotham’s quality, i.e., a crowned leader of Israel must be a righteous leader in the eyes of God and men, not an ambitious leader. The problem statement of the research is how does the narrator interweave and prove this thesis in the passage? The research purpose is to showcase the supporting literary elements in the narration as well as to prove the narrator’s thesis statement. The method that the writer uses in this writing is literary research. The writer analyzes primary resources that discuss the text of Judges 9:7-21. Besides that, the writer exegetes the text deeply while paying close attention to text analysis, historical and cultural background, and literary analysis. The research results in the fact that the narrator has succeeded to prove his thesis through the above discussed literary elements.Keywords: Judges 9:7-21, Abimelech, Jotham, word study, historical analysis, literary analysis. AbstrakDalam narasi Hakim-hakim 9:7-21, Yotam adalah figur yang inferior dibandingkan dengan Abimelekh yang pada waktu itu tengah menjadi penguasa. Tetapi justru di sinilah letak keindahan penulisan narasi tersebut. Narator ingin membalik dan mengusung tesis yang mengkritisi kepemimpinan Abimelekh, sekaligus memuji kualitas Yotam, yaitu bahwa pemimpin yang dinobatkan menjadi raja atas Israel harus merupakan pemimpin yang benar di mata Allah dan manusia, bukan pemimpin yang ambisius. Rumusan masalah dalam penelitian ini ialah bagaimana narator mengemas dan membuktikan tesis ini dalam penulisan perikop tersebut? Tujuan penelitian ialah untuk menunjukkan elemen-elemen sastra yang mendukung dalam narasi ini sekaligus membuktikan tesis narator. Metode yang penulis tempuh dalam penelitian ini ialah penelitian pustaka. Penulis mengkaji sumber-sumber pertama yang mengulas teks Hakim-hakim 9:7-21. Selain itu, penulis juga melakukan eksegesis mendalam terhadap teks dengan memperhatikan analisis teks, latar belakang sejarah dan budaya, serta analisis sastra. Hasil dari penelitian ini menunjukkan bahwa narator berhasil membuktikan tesisnya melalui elemen-elemen sastra yang dikaji di atas.Kata-kata Kunci: Hakim-hakim 9:7-21, Abimelekh, Yotam, analisis kata, analisis sejarah, analisis sastra